The 'America First' Policy and Illegal Immigrants: A Review of the Impact on Bilateral Cooperation between the United States and Mexico in 2025 - Atmaja, Shiffa Rindi (CV. Publikasi Indonesia, 2025)
This research aims to analyze the impact of the 'America First' policy, particularly with regard to illegal immigrants, on bilateral cooperation between the United States (US) and Mexico in 2025. The 'America First' policy that focuses on border security and immigration enforcement is expected to put pressure on US-Mexico relations, especially in the areas of trade, security, and border management. Through a qualitative case study approach, this research will examine how changes in US immigration policy affect the dynamics of cooperation in various sectors, including the economic impact of immigration restrictions, the security implications associated with increased activity at the border, and Mexico's response to the policy. The Mexican government is not solely responsible for the illegal movement of its citizens into the United States. The results of the study are expected to provide a deeper understanding of the challenges and opportunities in the US-Mexico bilateral relationship amid the 'America First' policy, as well as provide recommendations to maintain stability and sustainability of cooperation in the future.